Komunikasi Humor: Mengekspresikan Frustrasi tanpa Konfrontasi - Prasetya, Hendri (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2007)
Undoubtedly humor and laughing are essential parts of what if is to be human. All humor is fundamentally human activity. Humor is one of the most important form of creative human communication and expressive culture/ yet the formal study of humor and ifs social consequences has not enjoyed widespread popularity. Humor literature can be split info two broad categories: (a) why individuals use humor (mofivafional!y/psychological/y)and (b) the function humor within a social setting on society (sociologically)